Small-world brain networks in schizophrenia - 李名立 陈壮飞 李涛 (Shanghai Jingshen Yixue, 2012)
Over the last decade the combination of brain neuroimaging techniques and graph theoretical analysis of the complex anatomical and functional networks in the brain have provided an exciting new platform for exploring the etiology of mental disorders such as schizophrenia. This review introduces the current status of this work, focusing on the topological properties of human brain networks – called ‘small-world brain networks＇– and on the disruptions in these networks in schizophrenia. The evidence supporting the findings of reduced efficiency of information exchange in schizophrenia both within local brain regions and globally throughout the brain is reviewed and the potential relationship of these changes to cognitive and clinical symptoms is discussed. Finally we propose some suggestions for future research.